Transforming Healthcare through Intelligent Data Pipelines: A Technical Deep Dive - Sai Sravan Gudipati (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Healthcare institutions are experiencing a transformative shift through the integration of intelligent data pipelines and advanced analytics. This evolution encompasses the implementation of sophisticated streaming architectures, predictive monitoring systems, and robust security frameworks. The transition from traditional batch-processed electronic health records to real-time data processing has revolutionized patient care delivery and operational efficiency. Modern healthcare data architectures now handle massive volumes of heterogeneous data from multiple sources, including IoT devices, medical imaging systems, and laboratory information systems. The implementation of machine learning models and automated alert systems has significantly improved patient monitoring capabilities, reduced false alarms, and enhanced early detection of critical conditions. Advanced security measures, including multi-layered encryption and context-aware access control, ensure data privacy while maintaining operational efficiency. These technological advancements have resulted in reduced hospital readmission rates, decreased medication errors, and substantial cost savings through preventing adverse events.